A Rare Case: Unilateral Retinoblastoma in Adult Onset - Rani Yunita Patong; Suliati P Amir; Halimah Pagarra (Majalah Oftalmologi Indonesia, 2016)
Background: This study is to report a rare case of unilateral retinoblastoma in adultCase Illustration: A 40 years old woman presented to us with a complain of decreasing visual acuityin the right eye for 2 years. Ophthalmology examination revealed no light perception in the right eye,hyperemic conjunctiva, iris neovascularization, fixed pupil, and leukocoria. B-scan ultrasonographyexamination revealed a solid mass lesion without calcification and computerized tomography scanrevealed the right retrobulbar mass that infiltrated the right bulbus oculi. She underwent exenterationand the diagnosis was confirmed histopathologically.Conclusion: The diagnosis of retinoblastoma should be kept in mind in case presenting with proptoticor white mass lesion of unknown etiology in the fundus of an adult. Due to the aggressive nature ofthe tumor and metastatic potential, prompt diagnosis and management is essential.Â Keywords: retinoblastoma in adult, exenteration, immunohistochemistry